Effect of elasticity on the phagocytosis of micro/nanoparticles. Issue 12 (26th February 2020) - Yao, Chenyang; Akakuru, Ozioma Udochukwu; Stanciu, Stefan G.; Hampp, Norbert; Jin, Yinhua; Zheng, Jianjun; Chen, Guoping; Yang, Fang; Wu, Aiguo
Abstract : A broad range of investigation methods and frameworks are used to better study the elasticity of various micro/nanoparticles (MNPs) with different properties and to explore the effect of such properties on their interactions with biological species. Abstract : A broad range of investigation methods and frameworks are currently used to throughly study the elasticity of various types of micro/nanoparticles (MNPs) with different properties and to explore the effect of such properties on their interactions with biological species. Specifically, the elasticity of MNPs serves as a key influencing factor with respect to important aspects of phagocytosis, such as the clathrin-mediated phagocytosis, caveolae-mediated phagocytosis, macropinocytosis, and cell membrane fusion. Achieving a clear understanding of the relationships that exist between the elasticity of MNPs and their phagocytic processes is essential to improve their performance in drug delivery, which is related to aspects such as circulation lifetime in blood, accumulation time in tissues, and resistance to metabolism. Resolving such aspects is very challenging, and related efforts require using the right tools/methods, which are not always easy to identify. This review aims to facilitate this by summarizing and comparing different cell phagocytosis pathways, while considering various MNPs exhibiting different elastic properties, shape change capabilities, and their effect on cellular uptake. We conduct an overview of the advantages exhibited by different MNPs with respect to both in vitro and in vivo delivery, taking computational simulation analysis and experimental results into account. This study will provide a guide for how to investigate various types of MNPs in terms of their elastic properties, together with their biomedical effects that rely on phagocytosis.